Les présuppositions dans la publicité des produits alimentaires et des boissons en français sur YouTube : une étude pragmatique - Sausan Nailah; Sri Rejeki Urip; Anastasia Pudjitriherwanti (Lingua Litteria Journal, 2025)
This study aims to describe the types of presupposition in 13 French-language food and beverage advertisements on YouTube, as well as analyze the most dominant type of presupposition using George Yule's theory. The data collection technique uses listening and note-taking techniques, while the methods and analysis techniques used are pragmatic parsing method with the technique of sorting out the determining elements (PUP) and the advanced technique of Hinge Banding Differentiating (HBB) and mark reading technique. The result of the analysis shows that there are 41 utterances in the advertisements that contain presupposition. There are four types of presupposition found, namely existential (27 data), lexical (8 data), factive (4 data), and structural (2 data). The most dominant type of presupposition is existential because it is used to convey the existence of entities such as brands, products, ingredients, or benefits, thus building trust and positive perceptions of product quality.